Fabrication of silicon-vacancy color centers in diamond films: tetramethylsilane as a new dopant source. Issue 8 (7th February 2018) - Yang, Bing; Li, Junhao; Guo, Liang; Huang, Nan; Liu, Lusheng; Zhai, Zhaofeng; Long, Wenjing; Jiang, Xin
Abstract : A diamond film featuring a structure of nano-crystals separated with (100) micro-grains displays a maximum in the PL intensity of SiV centers. Abstract : Color centers in diamonds hold great promise for applications in optical sensors, bio-imaging, and quantum communication. Here, we synthesize Si-doped diamond films with Si-vacancy (SiV) centers by the flow of tetramethylsilane (TMS, Si(CH3 )4 ) gas using the microwave plasma chemical vapor deposition technique. In order to achieve high emission efficiency of the SiV centers, the effect of the TMS content on the microstructural evolution and photoluminescence (PL) of this type of color center is investigated using various spectroscopic techniques and high resolution transmission electron microscopy (HRTEM). The introduction of TMS gas in the diamond films leads to grain refinement of the diamond crystals and a weak SiV PL intensity located at 738 nm, at a growth temperature of 650 °C. For diamond films grown at 870 °C, the addition of Si atoms results in grain refinement and the transition of the diamond grains from micro-size without doping (no TMS) to nano-level at a Si/C ratio of 1/100. The SiV PL intensity exhibits a non-monotonic behavior with increasing Si/C ratios. At a Si/C ratio of 1/3100, the diamond film features a structure of nano-grains separated with (100) micro-grains, and displays a maximum in the PL intensity of the SiV centers: a very strong narrow peak at 738 nm with a FWHM of about 5.1 nm. Increasing the Si/C ratio promotes the formation of a nanocrystalline structure and the decrease of the SiV PL intensity. The combination of Raman spectral and HRTEM analysis implies that the PL quenching of the SiV center with the increasing Si/C ratios is attributed to the formation of amorphous carbon. Our results not only demonstrate that the diamond film, featuring a structure of nano-crystals with (100) micro-crystals, could be a promising material with high-efficiency SiV centers, but also highlight that this approach to balancing the concentration of Si impurities and the crystalline quality of the diamond films could advance the fabrication of high-emission SiV centers for optical applications.